Validity of computed tomography in diagnosing midfacial fractures. Issue 4 (April 2021) - de Carvalho, M.F.; Vieira, J.N.M.; Figueiredo, R.; Reher, P.; Chrcanovic, B.R.; Chaves, M.G.A.M.
Abstract: The aim of this study was to evaluate the sensitivity, accuracy, and reliability of two-dimensional computed tomography (2D-CT) scans (axial, coronal, sagittal planes) and three-dimensional computed tomography (3D-CT) reconstructions in diagnosing midfacial fractures in relation to actual fractures identified clinically and during surgery (gold standard). The imaging diagnosis was performed by a radiologist and an oral and maxillofacial surgeon. Sixty-two patients with a total of 429 midfacial fractures were included. Frontal sinus and nose fractures were easily diagnosed. For the three CT planes, there was a statistically significant difference between the CT examination and the gold standard for five to seven of the nine bones evaluated, while for 3D-CT, a difference was observed only for fractures of the orbital floor. The inter-observer agreement between the oral and maxillofacial surgeon and the radiologist was 75.5%. In conclusion, in this study 3D-CT reconstructions showed significantly the best sensitivity, accuracy, and reliability for the diagnosis of midfacial fractures. The sagittal reconstructions were the least diagnostic of the 2D-CT images. For areas where the parameters studied showed less agreement and hence a more difficult diagnosis, we recommend a combination of 3D and 2D-CT images to improve diagnostic accuracy.